Internal reliability, homogeneity, and factor structure of the ten-item Autism-Spectrum Quotient (AQ-10) with two additional response categories. (8th January 2021) - Shah, Punit; Bertrams, Alex
Abstract: The ten-item short form of the Autism-Spectrum Quotient (AQ-10) has been used to efficiently assess autistic traits in the general population; however, the psychometric properties of the AQ-10 in terms of its internal reliability and its unifactorial structure have recently been questioned. In the present study ( N = 797), whether the internal reliability is increased when the AQ-10 is applied with six rather than the conventional four response categories has been investigated. Moreover, correlational and confirmatory factor analyses were conducted to examine the reason for potential inhomogeneity within the AQ-10. The results suggest that the internal reliability of the AQ-10 was slightly increased but is still unsatisfactory, likely due to the incompatibility of items from two subdimensions: attention to detail and imagination. With six of the AQ-10 items, crucial aspects of the autistic personality may be measured, but other important aspects would be neglected; thus, the measure requires further psychometric development.